2013
DOI: 10.1007/s12088-013-0361-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening of lipid high producing mutant from rhodotorula glutinis by low ion implantation and study on optimization of fermentation medium

Abstract: In order to obtain lipid producing strain with high-yield, the wild type stain Rhodotorula glutinis was treated by low ion implantation, and optimization of fermentation medium for higher lipid yield was carried out using mutant strain. It was found that the strain had a higher positive mutation rate when the output power was 10 keV and the dose of N ? implantation was 80 9 2.6 9 10 13 ions/cm 2 . Then a high-yield mutant strain D30 was obtained through cid-heating coupling ultrasonic method and lipid yield wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…The constant pH 4 profile was also observed for the production of lipids by R. glutinis, during 10 to 11 days of fermentation, the pH and the production of lipids and biomass were simultaneously decreased, due to the yeast autolysis process, in turn, due to scarcity of nutrients [35]. In our studies, no decrease in these responses was observed up to 168 h.…”
Section: Confirmation Experimentssupporting
confidence: 78%
“…The constant pH 4 profile was also observed for the production of lipids by R. glutinis, during 10 to 11 days of fermentation, the pH and the production of lipids and biomass were simultaneously decreased, due to the yeast autolysis process, in turn, due to scarcity of nutrients [35]. In our studies, no decrease in these responses was observed up to 168 h.…”
Section: Confirmation Experimentssupporting
confidence: 78%
“…Profile of fatty acids synthesized by the R. glutinis primarily depends on the yeast strain and composition of the culture medium (Zhang et al 2011 ) (Table 2 ). However, the composition of the lipids can also be adjusted by modifying the molar ratio C/N in the culture medium (Braunwald et al 2013 ), temperature of cultivation (Suutari et al 1990 ), and by genetic modification of yeast (Shichang et al 2013 ). A significant impact on the profile of fatty acids synthesized by the R. glutinis yeast has also time of cultivation (Mast et al 2014 ; Zhang et al 2011 ).…”
Section: Fatty Acid Profile Of Lipids Synthesized By R Glumentioning
confidence: 99%
“…Lipids synthesized by R. glutinis can be also enriched in linoleic acid through genetic modification. Shichang et al ( 2013 ) used for this purpose implantation of nitrogen ions. The obtained mutant D30 synthesized almost 3-fold more linoleic acid (27 %) compared to the parental strain R. glutinis 31,596 (9.93 %), while significantly reduced oleic acid (from 61.8 to 49.3 %) and palmitic acid (from 5.66 to 11.0 %).…”
Section: Fatty Acid Profile Of Lipids Synthesized By R Glumentioning
confidence: 99%
“…Mn 2+ is an essential trace element for microbial growth that improves the activity of cellulase and yeast (Saxena and Tanner 2011;Lakkana et al 2012). The increase in activity and cellulose content is favorable for fermentation (Li et al 2013;Deesuth et al 2015). The results showed that the ethanol yield from cornstalks was improved by adding appropriate amounts of Mn 2+ , which was economically feasible.…”
Section: Process Optimization Of Ethanol Production From Cornstalksmentioning
confidence: 99%
“…The media were prepared as described by Li et al (2013). Medium I was used for slant medium, and it was composed of 10% wort with 2% agar and 2% peptone.…”
Section: Preparation Of the Slant Seed Fermentation Mediummentioning
confidence: 99%